Extraesophageal Reflux: What Is the Best Parameter for pH-Monitoring Data Analysis from the Perspective of Patient Response to Proton Pump Inhibitors? - Karol Zelenik; Petr Matousek; Miroslav Tedla; Jakub Syrovatka; Pavel Kominek (Gastroenterology Research and Practice)
Objectives. To analyze the pH-monitoring records of patients with suspected extraesophageal reflux (EER) using three different parameters (number of refluxes (NOR), acid exposure time (AET), and reflux area index (RAI)), with a view to determining which type of analysis is best at selecting the patients who will respond to a proton pump inhibitor (PPI). Methods. Demographic data were obtained and the level of the complaint was assessed using the Visual Analogue Scale. A dual probe pH-monitoring study was conducted. NOR greater than six, AET more than 0.1%, and RAI higher than 6.3 mpH were taken to be the thresholds for EER. Subsequently the response to a 12-week PPI trial was analyzed. Results. A total of 81 patients were analyzed. The percentages of patients with substantial EER based on NOR, AET, and RAI were 36%, 28% and 26%, respectively. Statistically significant, often positive PPI trials were confirmed in the group identified as having substantial EER using all three types of analysis. When using AET and RAI, the significance was more pronounced (P=0.012 and P=0.013, resp.) in comparison with NOR (P=0.033). Conclusions. Patients with EER diagnosed using AET or RAI will respond to PPI significantly often.